Strengthening food security through alternative carbohydrates in the city-state of Singapore - Lin, Amy Hui-Mei; Gómez-Maqueo, Andrea (Frontiers in Sustainable Food Systems, 2023)
Strengthening food security, where land and natural resources are limited or no longer available, is challenging, and this is especially true with producing staple food carbohydrates. Unlike some novel foods, i.e., culture meats, producing food carbohydrates using the conventional agri-food approach requires many natural resources, which are not available to some regions such as Singapore. Therefore, we must think out-of-box to enhance food availability, in terms of quantity and nutritional quality, in a sustainable manner. In this article, we reviewed current developments in food security in the city-state of Singapore and emphasized the essential role of food carbohydrates in the food security plan. We discussed the technology development (i.e., indoor farming, urban farming) used to enhance crop quality and production. We also made a few recommendations: exploring underutilized and unconventional crops that are resilient and nutrient-dense, identifying hidden resources in local ecosystems (i.e., revalorization agri-food processing by-products), and producing novel carbohydrates (i.e., microbial and synthetic carbohydrates). Experience and approaches in Singapore provide an example to other regions facing land and natural resource challenges and inspire creativeness in secure food availability.